Analisis Kemampuan Minyak Isolasi Transformator Daya Merek Unindo Dengan Pengujian Dissolved Gas Analysis dan Breakdown Voltage di Gardu Induk Serpong - Christiono; M. Reza Hidayat (EPSILON: Journal of Electrical Engineering and Information Technology, 2020)
The increasing demand for electric energy will always coimcide with increasing equipment performance at electrical substation. Power Transformer is one of the tools that really feels the impact, namely the increasing temperature of it is conductor in the form of transformer windings. That is the reason why the transformer has insulation in it, in the form of cellulose paper and transformer oil. To know the indication of failure on the transformer, we can test one of the transformer insulation, namely transformer oil. By doing the DGA testing and Breakdown Voltage of Transformator Oil Testing. After doing the DGA test by analyzing the testing result using TDCG, Key Gas, Doernenburg Ratio, Rogers Ratio, and Duval Triangle Methods. It can be seen that transformer 1 and 3 have experienced a failure indication in the form of temperature failure (Thermal Fault). It can be seen from the high content of methane and ethane gas. And after testing the voltage of the transformer oil breakdown, it can be seen that the condition of the transformer oil breakdown voltage 1 and 3 in the first test are still in good condition. Contrast with the second test, value of the breakdown voltage from both transformer are very bad. That is because the distance between the time of sampling with the testing is very far away and it causes many contaminans in the transformer oil.